2020
DOI: 10.1111/myc.13174
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing, in vitro susceptibility and virulence of Cryptococcus neoformans/Cryptococcus gattii species complex clinical isolates from south‐eastern Brazil

Abstract: Summary Background Cryptococcus neoformans/ Cryptococcus gattii species complex is composed of encapsulated yeast species that are causative agents of cryptococcosis. The characterisation of pathogenic Cryptococcus species provides useful data for epidemiological studies as well as the clinical diagnosis and treatment of patients. Objectives This study aimed to characterise the epidemiology, antifungal susceptibility and virulence of 72 clinical strains isolated from cryptococcosis cases between 2012 and 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…We performed the traditional three major virulence factor assays on all strains and found that all clinical isolates were able to grow well at 37°C, which showed the ability of the strains to consistently infect animals. However, the ability to grow at 39°C did not correlate with differences in virulence, and also the results showed that melanin production capacity and capsule size did not show a correlation with virulence either, similar to previous studies [11]. This also suggests that virulence was a very complex process and that a single phenotype among strains could hardly fully reflect the differences in virulence of strains.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We performed the traditional three major virulence factor assays on all strains and found that all clinical isolates were able to grow well at 37°C, which showed the ability of the strains to consistently infect animals. However, the ability to grow at 39°C did not correlate with differences in virulence, and also the results showed that melanin production capacity and capsule size did not show a correlation with virulence either, similar to previous studies [11]. This also suggests that virulence was a very complex process and that a single phenotype among strains could hardly fully reflect the differences in virulence of strains.…”
Section: Discussionsupporting
confidence: 86%
“…The ability to adapt and survive at 37°C is crucial for C.gattii to infect the host[10]. Its capsule not only inhibits phagocytosis by host phagocytes but also inhibits dendritic cell maturation and disguises antigen recognition [11]. Melanin is a reactive oxygen species (ROS) scavenger, which protects fungal pathogens from host immune responses [12].…”
Section: Introductionmentioning
confidence: 99%
“…This non-mammalian model can be maintained easily and inexpensively in laboratory conditions, at different temperatures, including the human temperature 37 • C. Similarly to mammalian models, this insect develops a specific immune response against different microbial infections (Pereira et al, 2018). Therefore, this insect has been used to study the fungal virulence and pathogenesis (Benaducci et al, 2016;Firacative et al, 2020;Grizante Barião et al, 2020) and to evaluate the efficacy of the antifungal agents against different fungal species (Singulani et al, 2019;de Castro Spadari et al, 2020). The results reported in the present study showed that early treatment with EAF from P. pluviosa combined with AmB was effective in controlling C. neoformans infection with no toxicity to larvae, supporting the in vitro results.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic make-up allowed some Cryptococcal spps. advantaged metabolic fitness, as was tested in pre-clinical models [33][34][35]. Mutated species of HIV may also play roles in the pre-treatment drug resistance to non-nucleoside reverse transcriptase inhibitors ART, and in alterations of immune responses after ART initiation [36].…”
Section: Pathogen-related Risk Factorsmentioning
confidence: 99%
“…Microbiological clearance is measured as log 10 clearance of Cryptococcus yeasts per mL of CSF and serves as an important predictor of increased mortality, including that from C-IRIS [49]. Cultured isolates can subsequently be serotyped by real-time PCR assay, and mating type can be determined by amplified fragment length polymorphism (AFLP) or PCR-restriction fragment length polymorphism (PCR-RFLP) [34,50]. Molecular typing revealed that genotypes, drug susceptibility, and the virulence of Cryptococcus species varied between different continents and in different countries [51].…”
Section: Pathogen-related Risk Factorsmentioning
confidence: 99%